Unraveling the Transcriptional Basis of Temperature-Dependent Pinoxaden Resistance in Brachypodium hybridum - Matzrafi, Maor; Shaar-Moshe, Lidor; Rubin, Baruch; Peleg, Zvi (Frontiers in Plant Science, 2017)
Climate change endangers food security and our ability to feed the ever-increasing human population. Weeds are the most important biotic stress, reducing crop-plant productivity worldwide. Chemical control, the main approach for weed management, can be strongly affected by temperature. Previously, we have shown that temperature-dependent non-target site (NTS) resistance of Brachypodium hybridum is due to enhanced detoxification of acetyl-CoA carboxylase inhibitors. Here, we explored the transcriptional basis of this phenomenon. Plants were characterized for the transcriptional response to herbicide application, high-temperature and their combination, in an attempt to uncover the genetic basis of temperature-dependent pinoxaden resistance. Even though most of the variance among treatments was due to pinoxaden application (61%), plants were able to survive pinoxaden application only when grown under high-temperatures. Biological pathways and expression patterns of members of specific gene families, previously shown to be involved in NTS metabolic resistance to different herbicides, were examined. Cytochrome P450, glucosyl transferase and glutathione-S-transferase genes were found to be up-regulated in response to pinoxaden application under both control and high-temperature conditions. However, biological pathways related to oxidation and glucose conjugation were found to be significantly enriched only under the combination of pinoxaden application and high-temperature. Analysis of reactive oxygen species (ROS) was conducted at several time points after treatment using a probe detecting H2O2/peroxides. Comparison of ROS accumulation among treatments revealed a significant reduction in ROS quantities 24 h after pinoxaden application only under high-temperature conditions. These results may indicate significant activity of enzymatic ROS scavengers that can be correlated with the activation of herbicide-resistance mechanisms. This study shows that up-regulation of genes related to metabolic resistance is not sufficient to explain temperature-dependent pinoxaden resistance. We suggest that elevated activity of enzymatic processes at high-temperature may induce rapid and efficient pinoxaden metabolism leading to temperature-dependent herbicide resistance.